Decentralized Traceability and Direct Marketing of Agriculture Supply Chains with QR Scanner - S. Syed Basha; S. Muni Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Food safety and agricultural supply chain transparency are more important than ever in today’s globalized world. It becomes increasingly challenging to keep track of the origin, quality, and progress of crops all the way through the supply chain as the complexity of agricultural systems that involve a variety of stakeholders grows. I consider blockchain to be a ground-breaking solution to these issues as a student studying contemporary technologies. Blockchain enables decentralized traceability, meaning all crop-related information—from planting to harvesting and delivery—is securely recorded and cannot be altered. Without the need for a centralized authority or intermediaries, this builds trust among buyers, sellers, and producers. The proposed platform uses blockchain to not only track crop prices and growth stages but also helps farmers directly market their products, boosting their profits and reducing dependency on middlemen. With QR scanners, consumers can quickly access the complete history of a product, including its origin and compliance with quality standards. Food safety is improved, corruption is reduced, and the supply chain as a whole becomes more reliable and efficient as a result of this transparency. By promoting trust, efficiency, and accountability at every stage of the food journey, this blockchain-based strategy represents a smart, futuristic approach to resolving real-world agricultural issues.